What If I Were the Exile? Linking Past and Present for Democratic History Teaching with Pre-Service Educators - María Belén San Pedro Veledo; María Luisa Zagalaz-Sánchez; Carmen González González de Mesa (MDPI AG, 2024)
The academic literature has fostered a debate in recent decades regarding the concept of historical empathy and the typology of activities that can help to treat and develop it, although there is no consensus as to the real effectiveness of narrative activities of a descriptive type that involve the projection of the person into the past. The aim of this research was to check whether the implementation of a programme that uses historical contextualisation, contact with primary testimonies, the use of sources and historical empathy, linking the situation of the exiles of the Spanish Civil War with the current refugees, can contribute to the development of tolerant attitudes towards the figure of the displaced in pre-service teachers and the degree to which these attitudes are modified after the application of the programme. The research design is quantitative and corresponds to a quasi-experimental design with a control and experimental group. A questionnaire was used to measure the attitudes of 101 pre-service teachers at a Spanish university towards refugees. The questionnaire was completed at two different times, before and after a historical empathy exercise on the exiles of the Spanish Civil War. The results indicate that programmes using historical contextualisation, testimonies close to refugees and historical empathy relating the situation of refugees to that of the exiles of the Spanish Civil War can contribute to increasing and/or reinforcing positive attitudes towards refugees in pre-service teachers.